IMPLEMENTASI PEMBIASAAN ṢALĀT ḌUḤĀ DALAM RANGKA PEMBINAAN AKHLAK SISWA DI SMPN 1 PATROL KECAMATAN PATROL KABUPATEN INDRAMAYU - Puspita Sari, Rina (2014)
This research is titled: "The implementation of ḍuḥā prayer to improve the best students attitude of SMPN 1 Patrol Kecamatan Patrol Kabupaten Indramayu". Department of Nation education purpose curriculum 2004 whics based of competence. One of this part is the best structure of curriculum 2004. It consist of structure of curriculum 2004 grade SD/MI, SMP/MTS and SMA/MA. The first to third grade of SMP/MTS class VII-IX given time 2 hours/week. One of way to increase behaviour of the best students attitude. It means quality of life that grows based of spirit value, the best behaviour attitude implementation. The implementation of this, we can do in habitual action like relation us God comunication, social comunication and nature by the implementation of ḍuḥā prayer. Students do the ḍuḥā prayer rarely, because they don't have much time to do it in daily. So, how to increase and improve the students doing ḍuḥā prayer? The purpose from this research to describe implementation of ḍuḥā prayer to improve the best students attitude of SMPN 1 Patrol. The term is to describe implementation of ḍuḥā prayer, the method of research is descriptive and qualitative method, collect the data, interview, observation. There are 3 parts to collect the data, reduction, explanation, and verification. Implementation of ḍuḥā prayer in SMPN 1 Patrol is done on Friday at 07.00-08.00 and must be report leader school. The impaced of students when prayer ḍuḥā is shape they sincere in every activity, resignation, discipline, cleanliness, relationship, similarity, and be attracted to comfort Allah SWT.